فعالة تعليم مهارة الكلام باللغة العربية أثناء الوباء كوفد 19 عبر الإنترنت - Faris Maturedy; Ahmad Hafidz Abdullah; Shelly Fuadatuz Zahra (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
The government has issued a policy in which schools require their students to study at home. Starting in March, the school implemented the online learning. This research aims to find out the effectiveness of online education in the era of the Covid-19 epidemic in teaching speaking skill at the Department of Arabic Language Teaching at the State Islamic University Jember. This research used the quantitative approach using the semi-experimental method. The method of data collection is the questionnaire, and the data was analyzed from the effectiveness of the test using N-Gain Score. The results of this research are It is said that online learning of speech skill is less effective, and the results of the performed calculations are 43%. According to the criteria of the N-Gain Interpretation which states that if the percentage value is 40-55, it means